Моделирование обобщенного эколого-экономического межотраслевого баланса с запаздыванием - Бойчук, М.В.; Шмурыгина, Н.М. (Кибернетика и системный анализ, 2009)
For a generalized static model of interindustry balance, a solution is found with allowance for the contamination control with delay; the optimum trajectory is specified by a piecewise-differentiable function over [t0,T] , and the optimum management is described by a piecewise-continuous function over a segment [t0,T] An algorithm for solution of the problem is developed and the results of computational modeling are presented. Для статичної узагальненої моделі міжгалузевого балансу із запізненням з урахуванням контролю над забрудненням знайдено розв’язок, причому оптимальна траєкторія — кусково-диференційована функція на [t0, T], а оптимальне керування — кусково-неперервна функція на відрізку [t0, T]. Розроблено алгоритм розв’язання задачі і наведено результати чисельного моделювання.